Perencanaan Pembelajaran Pendidikan Agama Kristen Melalui Teori Behavioristik: Christian Religious Education Lesson Planning Through Behavioristic Theory - Yohana Penina Zefanya Ribka; Yusak Tanasyah; Juan Tan (MODERATE: Journal of Religious, Education, and Social, 2023)
In the teaching and learning process, students as learners and teachers as educators play essential roles. Every student requires a comfortable and conducive learning atmosphere. Each student possesses unique and diverse learning characteristics. The question arises whether a teacher should follow each student's individual learning pattern. In any case, learning necessitates methods and strategies that ensure the teaching and learning process runs smoothly and achieves its objectives. The implementation can be either systematic or less structured, which will be observable during classroom activities. Furthermore, various learning media are needed to convey difficult discussion points. This study specifically addresses the process of Christian Religious Education (CRE). To achieve learning objectives, the author employs behavioristic theory within the CRE learning process. The writing method used is a library study (literature review). Contribution: This study contributes a practical framework for integrating behavioristic theory—specifically stimulus-response and reinforcement—into Christian Religious Education lesson planning to systematically foster observable behavioral change aligned with spiritual transformation.    Dalam proses belajar mengajar, tentu terdapat peran peserta didik sebagai pembelajar dan guru sebagai pendidik. Setiap peserta didik memerlukan suasana belajar yang nyaman dan kondusif. Setiap peserta didik memiliki karakteristik belajar yang unik dan berbeda. Apakah seorang guru sebagai pendidik harus mengikuti alur atau pola belajar setiap peserta didik? Dalam pembelajaran, diperlukan metode dan strategi agar proses belajar mengajar berlangsung dengan baik dan mencapai tujuan. Bentuk pelaksanaannya, baik teratur maupun tidak teratur, akan terlihat selama proses pembelajaran di kelas. Selain itu, diperlukan berbagai media pembelajaran untuk menyalurkan atau menyampaikan bagian diskusi yang sulit dipahami peserta didik. Secara khusus, penelitian ini membahas proses Pendidikan Agama Kristen (PAK). Untuk mencapai tujuan pembelajaran, penulis menggunakan teori behavioristik dalam proses pembelajaran PAK. Metode penulisan yang digunakan adalah studi pustaka. Kontribusi: Studi ini memberikan kontribusi berupa kerangka praktis untuk mengintegrasikan teori behavioristik ke dalam perencanaan pembelajaran PAK. Kontribusi utamanya adalah menunjukkan bagaimana stimulus-respons dan penguatan dapat digunakan guru PAK untuk membentuk perubahan perilaku peserta didik yang teramati sekaligus mendukung transformasi iman.